RANCANG BANGUN DETEKSI BANJIR BERDASARKAN TINGKAT KETINGGIAN AIR DAN INTENSITAS HUJAN BERBASIS INTERNET OF THINGS (IOT) - Amelia, Helsi; Dewi, Ratna; Nita, Sri (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2026)
Flooding is a natural disaster that frequently occurs in various regions of Indonesia. It cause material losses as well as casualties, and significantly impact the lives of affected communities. To reduce these risks and damages, an early detection system that can monitor environmental conditions in real-time is needed. This study aims to design and implement a flood detection system based on the Internet of Things (IoT) by utilizing the JSN-SR04T ultrasonic sensor to measure water levels and a rainfall sensor to detect rainfall intensity. The data collected from the sensors is transmitted via LoRa E220 communication, which is known for its long-range capability and low power consumption. The system consists of a transmitter node and a receiver node, where the received data is analyzed to determine flood potential. In addition, the system is integrated with the Telegram platform to automatically send notifications to Telegram users. The test results show that the system is capable of accurately monitoring water levels and rainfall, and can provide timely alerts. Therefore, this system offers an effective solution to increase awareness of potential flood hazards.